Qualitative Quotes: The Prevalence and Effects of Survey Respondent Exemplars in Political News Coverage. (January 2020) - Gaskins, Ben; Barabas, Jason; Jerit, Jennifer
National newspapers regularly report on public opinion as part of their political coverage. In addition to covering aggregate survey trends, journalists occasionally conduct follow-up interviews with respondents from those surveys to present the views of real people in news stories. The practice of reporting these "qualitative quotes" has existed for decades, yet, there has been little scrutiny of the voices that appear in news stories or their effect on public opinion. We examine this phenomenon in the context of the United States with a historical examination of New York Times stories and other major U.S. outlets that contain polling information and follow-up interviews. Consistent with past work on exemplars, there is considerable evidence for the nonrandom nature of the people invited to comment for news stories. In particular, the use of qualitative quotes reinforces some of the biases that exist in news sourcing more generally. Finally, we demonstrate in an experiment that qualitative quotes influence policy attitudes as least as much as aggregate polling figures.